In vitro effect of Bauhinia purpurea on glucose uptake activity in human hepatocellular carcinoma cells - Nusrah Husna Binti Muhtar.
Introduction: Diabetes is a condition characterized by derangement in carbohydrate, fat and protein metabolism, where glucose cannot enter the body's cells to be used as energy due to insulin deficiency or insulin resistance or both. Nevertheless, it has been reported that many synthetic drugs is responsible for various side effects such as flatulence and diarrhoea. In recent studies, many hypoglycemic agents have been introduced from traditional plants to solve this problem. One of them is Bauhinia purpurea. It is reported to contain flavonoids which exhibit various pharmacological activities such as lipid-lowering and hypoglycemic activity. Objective: The present investigation is to carry out the study of anti-diabetic effect of the aqueous leaf extract of Bauhinia purpurea in HepG2 cells by measuring glucose uptake of these cells. Hypothesis: Bauhinia purpurea are able to exhibit anti- hyperglycaemic property by inducing glucose uptake of HepG2 cells. Materials and method: Dried grinded leaves of Bauhinia purpurea was boiled in distilled water (dH2O) and filtered. The filtrate is then subjected to freeze drying. The powered extract were reconstituted in water at three different concentrations. In this study, HepG2 cells were cultured in DMEM media in 24 well plate with the presence of treatment BPAE (0, 0.01, 0.1, and 1 mg/ml) or insulin (0.1 unit/ml) and followed by the addition of H3-labelled glucose for 15 minutes incubation. Insulin was used as positive control group. Reaction stopped with cold PBS and cells were lysed with SDS. Radioactivity of lysed cells were measured using beta scintillation counter. This experiment was repeated for two times. Counted radioactivity was analysed. ANOVA were used to test the significant effect of different doses extracts on glucose uptake of HepG2 cells. Duncan Multiple Range test were used to compare means between the treatments significant at p (<0.05). Results: ANOVA test showed that the extract significantly in fluent the relative glucose uptake in HepG2 cells. The means value for glucose uptake of HepG2 treated with extract at 0.01, 0.1, 1.0 mg/ml were 1.03, 0.76, 0.27 folds respectively compared to control (0.0 mg/ml). The means value of glucose uptake is the lowest in 1.0 mg/ml while the rest of treatment concentrations is similar. Conclusion: This preliminary study showed that BPAE has no anti-diabetic effect.